The students creative thinking on environmental pollution material using video-assisted problem based learning model - Nyoman Trijaya Kusuma; Dina Maulina; Wisnu Juli Wiyono (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
The ability to think creatively has an important role in 21st century learning. This study aims to determine the effect of applying the video-assisted Problem Based Learning (PBL) model on the creative thinking skills of class VII students of SMP Negeri 1 Sekampung Udik on environmental pollution material. The research sample was selected by purposive sampling technique. The design of this study used a quasi-experimental design with a non-equivalent control group design. The type of data taken is quantitative data and qualitative data. Quantitative data in the form of mean values of pretest, posttest, and N-gain ability to think creatively tested using the Independent Sample t-Test with a significance level of 5% obtained Sig. (2-tailed) 0.00 <0.05. Qualitative data in the form of a questionnaire on student responses to the use of the video-assisted PBL model. The results showed that the N-gain value for the experimental class was 0.57 in the "medium" category and the control class was 0.29 in the "low" category. These results indicate that there is a significant effect of using the video-assisted PBL model on students' creative thinking abilities in environmental pollution material. Student responses showed a positive response with an average score of 71.2% in the "good" category. Therefore, it can be concluded that the application of the video-assisted PBL model has an effect on the creative thinking abilities of students.Abstrak. Kemampuan berpikir kreatif memiliki peranan penting pada pembelajaran abad 21. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan model Pembelajaran Berbasis Masalah (PBL) berbantu video terhadap kemampuan berpikir kreatif siswa kelas VII SMP Negeri 1 Sekampung Udik pada materi pencemaran lingkungan. Sampel penelitian dipilih dengan teknik purposive sampling. Metode penelitian ini menggunakan quasi eksperiment dengan bentuk desain penelitian non-equivalent control group design. Data kuantitatif berupa rerata nilai pretest, posttest, dan N-gain kemampuan berpikir kreatif yang diuji menggunakan uji Independent Sample t-Test dengan taraf signifikansi 5% didapatkan nilai Sig. (2-tailed) 0,00 < 0,05. Data kualitatif berupa tanggapan peserta didik pada penggunaan model PBL berbantu video. Hasil penelitian menunjukan bahwa nilai N-gain kelas eksperimen mencapai 0,57 dengan kategori “sedang” dan kelas kontrol mencapai 0,29 dengan kategori “rendah”. Hasil tersebut memperoleh terdapat pengaruh yang signifikan penggunaan model PBL berbantu video terhadap kemampuan berpikir kreatif siswa pada materi pencemaran lingkungan. Respon peserta didik terhadap pembelajaran menunjukan respon yang positif dengan rata-rata nilai 71,2% dengan kategori “baik”. Dengan demikian, disimpulkan bahwa penerapan model PBL berbantu video berpengaruh terhadap kemampuan berpikir kreatif siswa.